PENGARUH KEPUASAN PELANGGAN DAN PERSEPSI PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA UD PN SILITONGA SERBELAWAN - Wenty Panjaitan; Darwin Lie; Marisi Butarbutar; Ady Inrawan (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2018)
As for this research problem formula is how the influence of customer satisfaction and customer perceptions of loyalty of customers on UD PN Silitonga Serbelawan. The results of this research can be summarized as follows: 1. Customer satisfaction is satisfied, customer perception is good, customer loyalty is good. 2. Multiple linear regression analysis is Ŷ = 3,545 + 0,285X1 + 1,140X2 meaning customer satisfaction and customer perception have positive influence on customer loyalty. 3. Correlation analysis obtained r = 0.690 it is means there is high and positive in correlation between customer satisfaction, customer perceptions, with customer loyalty. Obtained coefficient of determination R square 0,476, meaning high customer loyalty equal to 47,6% can be explained by customer satisfaction and customer perception while the rest equal to 52,4% influenced by other factor. 4. Hypothesis test results stated H0 rejected, meaning customer satisfaction and customer perceptions have a positive and significant influence on customer loyalty at UD PN Silitonga Serbelawan either simultaneously or partially. Keywords: Customer Satisfaction, Customer Perceptions, and Customer Loyalty